"A onda do mar leva, a onda do mar traz": a poética praiana de Dorival Caymmi como emblema da identidade nacional - Luna, Glauber Barreto (2021)
This work analyzes the social processes that enabled Dorival Caymmi and her beach poetics to be consecrated as emblems of national identity. Assuming that, on the one hand, Caymmi found, during the first half of the 20th century, a sociocultural situation favorable to the good reception of his “praieiras songs”; on the other, there were investments (material and symbolic) by the artist himself and other agents (belonging to the artistic, intellectual, economic and political fields related to him) regarding the consolidation of his image as a symbol of "Brazilianness", it investigates how, in one way, the beach theme is shaping the national identity and, in another way, what were the social conditions conquered and offered to Caymmi and his work, so that both could become representatives of this theme. Through a qualitative research carried out through the analysis of a broad empirical material - interviews, songs, album covers, photographs (personal and professional), periodicals (newspapers and magazines), film documentaries, testimonials, etc., we sought to apprehend , from the Freyrean perspective of national identity, the conversion of Caymmi as “Singer of the seas of Bahia” to “singer of the seas of Brazil”.